1997
DOI: 10.1007/s002030050492
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic growth on carbon disulfide is a property of novel strains of Paracoccus denitrificans

Abstract: Three distinct strains (KL1, KS1, and KS2) of facultatively chemolitho-autotrophic bacteria able to use carbon disulfide or carbonyl sulfide as sole energy substrates were identified as novel strains of Paracoccus denitrificans. Evidence for their identity as biovars of P. denitrificans and as close relatives of Paracoccus versutus is based on their DNA composition, total sequencing of the genes for their 16S rRNA, muropeptide profiles, amino acid composition of peptidoglycan, kinetics of murein degradation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…This conclusion was also drawn by Goodhew et al (1996), who pointed out that the 'Stanier strain 381 ' cannot have given rise to both ATCC 17741T and DSM 65, as stated in the respective culture collection catalogues. The group B sequence was also identical to that reported for P. denitrykans strain LMG 4218 (sequence X69159) and for T. (Ludwig et al, 1993), and showed > 99 % similarity to the three carbon-disulfideusing strains recently classified as P. denitrzjicans DSM 11072, DSM 11073 and DSM 11104 (Jordan et al, 1997). The similarity between members of groups A and B was 98-1 YO in all cases.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…This conclusion was also drawn by Goodhew et al (1996), who pointed out that the 'Stanier strain 381 ' cannot have given rise to both ATCC 17741T and DSM 65, as stated in the respective culture collection catalogues. The group B sequence was also identical to that reported for P. denitrykans strain LMG 4218 (sequence X69159) and for T. (Ludwig et al, 1993), and showed > 99 % similarity to the three carbon-disulfideusing strains recently classified as P. denitrzjicans DSM 11072, DSM 11073 and DSM 11104 (Jordan et al, 1997). The similarity between members of groups A and B was 98-1 YO in all cases.…”
supporting
confidence: 75%
“…Beijerinck 1910), with other extant examples of the original isolate being LMD (Delft Collection of Microorganisms, Delft, The Netherlands) 22.2 lT, ATCC 19367 and ATCC 13543 (Davis et al, 1969). Numerous similar isolates were subsequently assigned to P. denitrificans, which became recognized as a heterogeneous species comprising several biotypes (Jordan et al, 1997;Van Verseveld & Stouthamer, 1992). A related single-species genus, Thiosphaera pantotropha (Robertson & Kuenen, 1983), was also assigned to P. denitrijicans on the basis of analysis of the base sequence of the 16s rRNA gene (Ludwig et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…denitrificans' appeared only in the seventh edition (Breed et al, 1957). For many years, P. denitrificans remained the only authentic species of Paracoccus, with the result that biotypes actually differing from each other at the species level were assigned to this species (Baj, 2000;Dobson & Franzmann, 1996;Kelly et al, 2000;Jordan et al, 1997;Nokhal & Schlegel, 1983;Van Verseveld & Stouthamer, 1992). An example was Thiosphaera pantotropha (strain GB17…”
mentioning
confidence: 99%
“…(Kelly & Wood, 1982;Kelly et al, 2000;Taylor & Hoare, 1969). Moreover, the ability to grow on carbon disulfide is a property of P. pantotrophus, not yet shown also to apply to P. denitrificans (Jordan et al, 1995(Jordan et al, , 1997Rainey et al, 1999).…”
mentioning
confidence: 99%